Adaptive Management Across Project Cycles: Look into Coherence in Time - Guerzovich, Florencia (Medium, 2023)
This is a series about Monitoring, Evaluating and Learning (MEL) whether sets of interventions/portfolios are adding more together than each one would produce on their own. In post 1, I pointed to coherence, the new OECD-DAC evaluation criteria as a way to bridge the ambition of bringing bigger change with the MEL world. In post 2, I shared 3 of 4 practical lessons I’ve learned in experimenting with MEL systems and exercises that focus explicitly on interactions of interventions/portfolios. In the third post, I bring Paul Pierson’s groundbreaking argument for social science to MEL. Paraphrasing, most contemporary MEL takes a “snapshot” view of interventions and portfolios, distorting their effects and meaning by ripping them from their temporal context. Instead, we should place in time interventions/portfolios with the ambition to add more than the sum of the part by constructing MEL systems looking at “moving pictures” rather than taking snapshots. ...

Evaluating complex interventions in international development - Masset, Edoardo; Shrestha, S.; Juden, M. (CEDIL Methods Working Paper 6, 2021)
This paper reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. Complex interventions are those that are characterised by multiple components, multiple stakeholders, or multiple target populations. They may also be interventions that incorporate multiple processes of behavioural change. While such interventions are very common and receive a large proportion of development aid budgets, they are rarely subject to rigorous evaluations. The CEDIL Methods Working Paper, ‘Evaluating Complex Interventions in International Development’, reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. The paper focuses its attention on methods that address causality and allow us to state conclusively whether an intervention works or not. It shows that several rigorous methods developed in different disciplines can be adapted and used to evaluate complex interventions in international development.

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press Publication, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS Policy Briefing, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.

Evaluating complex interventions: What are appropriate methods? - Masset, Eduardo (CEDIL, 2022)
In the CEDIL Methods brief, ‘Evaluating complex interventions: What are appropriate methods?’ we identify four types of complex development interventions: long causal chain interventions, multicomponent interventions, portfolio interventions, and system-level interventions. These interventions are characterised by multiple activities, multiple outcomes, multiple components, a high level of interconnectedness, and non-linear outcomes.